A parallel currency proposal for the stronger Euro-states - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2013)
It is argued that the stronger member states of the European Monetary Union should find their way out of the Euro in order to avoid being dragged into a disastrous course of inflation and over-indebtedness by the weaker members. A sudden exit would presumably cause financial turmoil as well as political damage and is, thus, no realistic option. However, by creating a parallel currency called Hard-Euro as an intermediate solution, there would indeed be a way of separating the EMU into two parts, with a weaker Euro in the southern countries and a stronger Euro in the northern countries. Using a small macro-model, the paper discusses this idea and its economic consequences in more detail. Following the early idea of separating the functions of money by Eisler (1932), the Hard-Euro is invented in the form of a pure book-money, while the Euro is still the only cash money until further notice. The Hard-Euro is designed as an index-currency such that its exchange rate exactly compensates for the inflation rate of the common Euro. Hence, it is absolutely stable in terms of consumer prices, and at the same time the exchange rate can never overshoot. By this means, savers in the stronger member states are protected from both inflation and financial repression, while the weaker member states can improve their competitiveness by inflating the Euro. It is shown, that this approach is likely to increase both investment and total output in the EMU. Later on, this intermediate regime could be substituted by the definite separation of the Euro-Zone into a stronger northern and a weaker southern part.
Keywords: 330